Oxidative and/or Inflammatory Thrust Induced by Silver Nanoparticles in Rabbits: Effect of Vitamin E or NSAID Administration on Semen Parameters - Collodel Giulia; Mattioli Simona; Moretti Elena; Cerretani Daniela; Micheli Lucia; Fiaschi Anna Ida; Menchetti Laura; Brecchia Gabriele; Castellini Cesare (Mediators of Inflammation)
The aim of this research was to evaluate the inflammatory and/or oxidative damage related to silver nanoparticles (AgNPs), which are responsible for negative effects on sperm physiology and metabolism. Thirty New Zealand White rabbit bucks were divided into 5 experimental groups (6 animals/group): Control, treated with 0.9% NaCl; AgNP, treated with a 5 mM AgNP solution; LPS, treated with 50 g/kg b.w. E. coli LPS; AgNPs + NSAID, treated with an anti-inflammatory drug at 0.2 mg/kg b.w. and 5 mM AgNPs; and AgNPs + Vit E, treated with 0.18 mg/kg b.w. vitamin E and 5 mM AgNPs. Sperm quality and oxidative and inflammatory status were assessed at different times (0-60 days). Two statistical models were built: the first evaluated the effects of AgNPs and LPS (vs. Control), whereas the second evaluated the protective effect of an NSAID and vitamin E against AgNP-induced damage. Three principal component analyses were performed: sperm traits (motility, volume), oxidative status (antioxidants, oxidative metabolites, and redox reactions), and cytokines (TNF-α, IL-8, and IL-6). A negative effect on reproductive traits resulted after NP administration. In particular, an inflammatory/oxidative response took place in the reproductive tract during the first 2-3 wks of AgNP administration (cytokine and oxidative metabolite generation); the inflammatory/oxidative thrust impaired the status of rabbit tissues (seminal plasma, sperm, and blood), inducing a response (increased antioxidant enzymes and redox reactions) at 4-7 wks; oxidative stress, if not totally counteracted, likely induced toxicity in the late phases of AgNP administration (8-9 wks). In conclusion, exposure to silver nanoparticles produced a similar but more persistent effect than that of LPS on rabbit reproductive tissues: AgNP administration triggered a proinflammatory response linked to oxidative thrust, worsening many sperm parameters. However, only anti-inflammatory treatment counteracted the negative effects of AgNPs, whereas vitamin E seemed to act as an adjuvant, attenuating the oxidative cascade.